1989
DOI: 10.1002/pola.1989.080270409
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of plasma polymerization of allylamine by FTIR

Abstract: SynopsisThe plasma polymerization of allylamine in an inductively coupled rf plasma reactor is analyzed by Fourier transform infrared spectroscopy. Comparison of the infrared spectra of the as-received monomer and the plasma polymerized f i l m reveals a conversion of the primary amine in the monomer (-CH,-NH,) to an imine (-CH=NH) and a nitrile (C-N). Plasma polymerization of ethylenediamine yields the same results, suggesting that this polymerization scheme may be typical of primary amines. Increasing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 9 publications
4
29
0
Order By: Relevance
“…In particular, PPAA is much less hydrogenated than the monomer. This was already observed by Krishnamurthy et al [11].…”
Section: Resultssupporting
confidence: 63%
“…In particular, PPAA is much less hydrogenated than the monomer. This was already observed by Krishnamurthy et al [11].…”
Section: Resultssupporting
confidence: 63%
“…This may also be due, in part, to some retention of the original double bond in the AA molecule after deposition of the AApp thin film and generation of unsaturated species during plasma deposition. Previous researchers have shown that the use of unsaturated monomers such as allylamine favors the formation of reactive unsaturated species such as imines and nitriles 46. Analysis of the high resolution carbon (C1s) spectra of the AApp (not shown) reveals a film that is rich in hydrocarbon and carbon‐nitrogen and carbon‐oxygen moieties such as amine and amide containing species.…”
Section: Resultsmentioning
confidence: 96%
“…It was found that the structure and chemical nature of the plasma-polymerized allylamine (PPAA) films depends on the plasma conditions [29][30][31][32]; different film properties can be generated from the same monomer. In particular, the crosslink density of the films is directly dependent on the plasma power used during the deposition process.…”
Section: Introductionmentioning
confidence: 99%